Avaliação da adaptação marginal de próteses implantadas provisórias manufaturadas de forma não digital, fresadas e impressas em 3D - Rodrigues, Thaís Cristina Mendes (2021)
Computer-aided manufacturing technology (CAD-CAM) allows for different manufacturing techniques. Little revised information is available on the performance in relation to marginal fit in milled manufacturing, 3D printing compared to non-digital methods (conventional). The aim of this in vitro study was to evaluate the marginal fit of implant-supported temporary prostheses that were manufactured in a non- digital way, milled and printed in 3D. Fifteen implant- supported temporary prostheses were produced, with 3 elements each one. The prostheses bridge was divided into three groups: five were performed in the laboratory in a non-digital way (GC); five produced in a milled system (PrograMill PM7, Ivoclar) (GM); and five were printed with thickness of 50 μm on the 3D printer LCD (Photon S, Anycubic) (GI). The samples were produced using de following resins: resin Vipicor (VIPI®) a conventional technique (GI), Telio CAD LT (Ivoclar Vivadent) (GM), Yller Cosmos Temp (Yller Biomaterials SA) (GI). Finishing and polishing processes were not carried out on the pieces and after, were stored in a dry environment, protecting from external light. The marginal fit was assessed using a scanning electron microscope images (SEM), resulting (n=15). Performed in 2 situations: only one central screw and with all screws tightened. The horizontal misfit values were divided into over, equal and under extended. Statistical analysis was performed using the Tukey Kramer test, with a significance level of 5%. In vertical and horizontal assessment, 3D printed prostheses showed a greater misfit than the milled ones and the control group (P<0.05). According to the limitations of an in vitro study, 3D printed prostheses presented the most unfavorable results than non-digital method and milled form in the evaluation of vertical and horizontal misfit.